18 Can a short training module improve nutritional knowledge of malnutrition by junior doctors?. (5th April 2017) - Musson, H; Rajasekhar, P; Thompson, N; Mountford, C; Gemmell, L; Davidson, B
Abstract : Background: Malnutrition is a major cause and consequence of poor health. Hospitalised patients are at increased risk of malnourishment; around 30% of people aged over 65 are at risk of malnutrition on admission. Additionally, malnutrition increases costs hugely to the NHS. Despite the prevalence and cost of this problem, formal teaching to junior doctors about malnutrition is limited. Aim: To assess whether an online training module could improve knowledge of nutritional management of hospitalised patients. Methods: Using SurveyMonkey, a survey was distributed to Foundation Year FY1 and FY2 doctors working at both Newcastle and Northumbria NHS Foundation Trainee (FT). The doctors were asked five questions, then given information relating to malnutrition. Finally they answered the five questions again. The survey took approximately 15 min to complete. Participants could then download a certificate to show involvement with training. Statistical analysis was performed using a paired t-test to assess the doctors' improvement in answering the questions. Results: 87 doctors participated. The results are outlined in the table below. A paired t-test was used to measure the difference in correct answers selected between the 1 st and 2 nd attempts, p-value of 0.013. Conclusions: Knowledge of malnutrition can be improved by completing a short training module. Future studies should address the technical issues of using SurveyMonkey within FTs and use larger sample sizes to prove the generalisability of the results. Improved knowledge should lead to earlier recognition and treatment of malnutrition with improved health outcomes and reduced costs.